2013
DOI: 10.6061/clinics/2013(06)19
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic H1N1 illness prognosis: evidence from clinical and epidemiological data from the first pandemic wave in São Paulo, Brazil

Abstract: OBJECTIVES:The pandemic of 2009 H1N1 influenza A emerged in February 2009, with high morbidity and mortality, and rapidly spread globally. São Paulo was among the most affected areas in Brazil. This study compares the clinical and epidemiological characteristics of influenza-like illness between outpatients and hospitalized patients and evaluates the impact of oseltamivir therapy on the outcome of 2009 H1N1 influenza A patients.METHODS:This is a case series study comparing the clinical and epidemiological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Srinivasa et al, 15 reported that common age group that suffered with H1N1infection was 21-30 years (60%) followed by 31-40 (30%). Bellei et al, 16 also confirmed the great burden of 2009 pandemic H1N1 infection among young adults.…”
Section: Discussionmentioning
confidence: 87%
“…Srinivasa et al, 15 reported that common age group that suffered with H1N1infection was 21-30 years (60%) followed by 31-40 (30%). Bellei et al, 16 also confirmed the great burden of 2009 pandemic H1N1 infection among young adults.…”
Section: Discussionmentioning
confidence: 87%